A COMPREHENSIVE STUDY OF BUSINESS OPERATIONS AND CONSUMER OUTREACH IN THE SUSTAINABLE RECYCLING INDUSTRY IN AHMEDABAD - Sharma, Deepak; Kulkarni, Sameer (International Journal of Engineering Technologies and Management Research, 2025)
India is one of the world’s largest producers of textile waste, generating over 5.2 million tonnes annually, of which less than 30% enters formal recycling streams. Ahmedabad, historically referred to as the ‘Manchester of India’, remains a major textile production centre and also one of the highest contributors to textile waste. This research examines operational practices, supply chain structures, and consumer behaviour within the sustainable textile recycling industry in Ahmedabad, with a detailed case analysis of ReVerse Green Clothing Pvt. Ltd. A mixed-method research design was implemented incorporating surveys (N=200), field observations, and interviews with industry stakeholders. Findings reveal that although awareness of environmental issues is rising, behavioural conversion toward recycling remains limited due to infrastructural gaps, inconsistent waste inflow, lack of segregation, and low accessibility of collection points. Youth-driven sustainable fashion adoption is increasing, reflecting changing consumer values. The study recommends enhanced reverse logistics, digital transparency, decentralised collection points, and public–private partnerships to scale the circular textile economy.